2022
DOI: 10.3390/en15155581
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Temperature Gradient on Chloride Ion Diffusion in Nuclear Reactor Containment Building Concrete

Abstract: Chloride diffusion through concrete is influenced by harsh environmental conditions such as high ambient temperature and relative humidity. This paper examined the influence of temperature gradient on chloride diffusion in concrete under high ambient temperature conditions. Chloride diffusion tests using cylindrical concrete samples were performed in constant temperature and temperature gradient conditions. In a temperature gradient condition, a much higher chloride concentration was measured than at constant … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 33 publications
(46 reference statements)
0
4
0
Order By: Relevance
“…The powder was then used to measure the chloride content by the potentiometric titration according to ASTM C1152/1152 M-04 (2012) standard. More details of the experimental setup for the chloride diffusion tests and the measurement of the chloride content in the concrete samples are referred to as An et al [4].…”
Section: Experimental Setup For Chloride Diffusion Tests Under the Te...mentioning
confidence: 99%
See 2 more Smart Citations
“…The powder was then used to measure the chloride content by the potentiometric titration according to ASTM C1152/1152 M-04 (2012) standard. More details of the experimental setup for the chloride diffusion tests and the measurement of the chloride content in the concrete samples are referred to as An et al [4].…”
Section: Experimental Setup For Chloride Diffusion Tests Under the Te...mentioning
confidence: 99%
“…Consequently, the service life of the concrete structures is shortened. Environmental factors such as temperature and relative humidity have been reported to affect the rate of chloride ion diffusion in concrete [3,4]. Furthermore, the concrete microstructural properties such as porosity and permeability play a major role in the diffusion of chloride ions in concrete.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…As such, a TG situation is created through the RCB walls. Previous studies have shown that the chloride ion diffusion increases significantly in concrete when the CG and TG are in the same direction [1,2]. However, none of these studies have extensively examined the effect of water-to-cement (w/c) ratio on chloride ion diffusion under CG and TG conditions.…”
Section: Extended Abstractmentioning
confidence: 99%